Evaluating the surface film’s properties based on acoustic emission and contact voltage signals - Trinh, Hiep Xuan; Dua , Tran Van; Quang, Ngo Van (Vietnam Journal of Science and Technology, 2021)
The methods of creating the hard coating films or lubrication are widely used to improve the quality of the machine part’s surface. The core of these methods is to generate the intermediate films on the surfaces of the machine’s parts. The adhesion properties of the coating films on the substrate and the pressure resistance of the lubricant layer are the most important characteristics of these intermediate films. This paper focused on evaluating those properties based on the data of acoustic emission and electrical contact voltage signal, obtaining from the scratch test, and pin-on-flat model.